Patient Perceptions of Surgeon Attire, Professionalism, and Gender Bias in Pakistani Public Hospitals - Maham Arshad; Zara Ali; Talha Tariq; Kainat Raza; Fatima Hashmi; Tarim Nayab (Journal of University College of Medicine and Dentistry)
Objective: Surgeon attire significantly influences patient perceptions of professionalism, competence, and trust. This study aims to assess public perceptions of formal and informal surgeon attire and to analyze gender biases in these perceptions among male and female surgeons.